Association Between Chest Radiograph Findings and Molecular Test in Paediatric Tuberculosis - Trisno Adhy Kusuma; Hafaz Zakky Abdillah; Ranti Permatasari; Fathia Meirina; Cynthea Prima Destariani; Rini Savitri Daulay (Indonesian Journal of Global Health Research, 2026)
Tuberculosis (TB) remains a major global health concern, with children representing a substantial proportion of cases. Diagnosis in paediatric populations is challenging due to non-specific clinical features and limited bacteriological confirmation, making chest radiography and molecular rapid tests essential. This study aimed to evaluate the association between chest radiographic abnormalities and molecular rapid test results in paediatric pulmonary TB patients. A retrospective cohort study was conducted at Haji Adam Malik General Hospital from January to May 2025, involving 60 children diagnosed with pulmonary TB. Data were collected through consecutive sampling, comprising demographic characteristics, chest radiographic findings, and molecular rapid test (GeneXpert). Statistical analysis was performed using the chi-square test to evaluate diagnostic parameters. Results: Among 60 patients (46.7% male; mean age 10 years), 48.3% showed abnormal chest radiographs, predominantly infiltrates (60%) and pleural effusion (23.3%). GeneXpert results were evenly distributed, with 30 positive and 30 negative cases. A significant association was found between radiographic abnormalities and molecular test results (p < 0.001). Diagnostic parameters for radiographs included sensitivity 0%, specificity 3.3%, and accuracy PPV 0% and NPV 3,2%. Chest radiography is useful for initial paediatric TB screening but less accurate than molecular tests.